Modeling of oil spill dispersion to improve management system for environmental protection of Port Rajee, Iran - Farzingohar, Mehrnaz (2014)
In the transfer of oil products from tanker to terminal the oil may spill from ruptured pipes, corroded valves and connectors and old equipment which may pollute water and air. Rajaee Port in the Persian Gulf is an important terminal for the Bandar Abbas Oil Refining Company (BAORCO). The major goals of this study are the identification of risk areas from trajectory and fate of the oil spills to the management system for contingency plans to protect the local environment. Two models are used. The General NOAA Oil Modeling Environment (GNOME) model is used for oil spill pollution in the sea and the Areal Location Of Hazardous Atmosphere (ALOHA) is applied to identify the trajectory of the evaporated oil spill through the air. The results from both models were analysed to determine the location of risk areas through the water and air around the spill. Previous studies of water and sediment samples analysis were compared and used to verify and validate the model results. The North east of Qeshm Island and the east of Rajaee Port were identified as the high risk areas. The results are used to improve plans which are implemented by BAORCO in order to reduce the negative environmental impacts.